2015
DOI: 10.3171/2015.5.peds15220
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric outcomes after pediatric sports-related concussion

Abstract: J neurosurg Pediatr 16:709-718, 2015 abbreviations ADHD = attention-deficit hyperactivity disorder; ICD-10 = International Classification of Diseases, 10th Revision; IQR = interquartile range; NOS = not otherwise specified; NPD = novel psychiatric disorder; OCD = obsessive-compulsive disorder; PCS = postconcussion syndrome; PCSS = Post-Concussion Symptom Scale; SRC = sports-related concussion; TBI = traumatic brain injury. obJect The objectives of this study were twofold: 1) to examine the prevalence of emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(148 citation statements)
references
References 57 publications
(99 reference statements)
3
142
0
Order By: Relevance
“…In rare cases, patients with vestibulo-ocular and cervicogenic PCD can experience mild exacerbation of their symptoms that typically occurs towards the later stages of exercise when walking at higher inclines. In some cases, PCS patients may develop clinical features that meet the International Classification of Headache Disease 3beta (ICHD-3B) criteria for new or worsening migraine headaches (83), while others may develop post-injury psychiatric outcomes including mood disorders (84). Although some patients will demonstrate symptoms of multiple or overlapping PCDs, the following classification system provides a conceptual framework that allows physicians to identify the pathophysiological mechanisms that govern persistent concussion symptoms and informs the development of individually tailored rehabilitation programs (see Tables 1 and 2; Figure 1).…”
Section: Supplemental Testingmentioning
confidence: 99%
“…In rare cases, patients with vestibulo-ocular and cervicogenic PCD can experience mild exacerbation of their symptoms that typically occurs towards the later stages of exercise when walking at higher inclines. In some cases, PCS patients may develop clinical features that meet the International Classification of Headache Disease 3beta (ICHD-3B) criteria for new or worsening migraine headaches (83), while others may develop post-injury psychiatric outcomes including mood disorders (84). Although some patients will demonstrate symptoms of multiple or overlapping PCDs, the following classification system provides a conceptual framework that allows physicians to identify the pathophysiological mechanisms that govern persistent concussion symptoms and informs the development of individually tailored rehabilitation programs (see Tables 1 and 2; Figure 1).…”
Section: Supplemental Testingmentioning
confidence: 99%
“…41 To date, the majority of published case reports on the retirement decision-making process in the setting of multiple concussions and prolonged recovery are limited to discussions regarding collegiate and professional athletes.…”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, acquired psychological symptoms commonly occur following injury. 15 Particular attention has been paid to the prevalence of depressive symptoms that co-occur with other persistent post-concussive symptoms. A study of previously healthy adults without psychiatric pre-morbidities at time of study enrollment who sustained mild traumatic brain injury indicated that 62.5% of patients with persistent post-concussive symptoms 1 year after injury had a modifiable psychological risk factor (i.e., depression, possible PTSD, and/or low resilience) at 1 month.…”
Section: Introductionmentioning
confidence: 99%
“…26 While it is accepted that a relationship exists between depressive and persistent post-concussive symptoms, it remains poorly understood how depressive symptoms change over time in conjunction with post-concussive symptoms in patients who are slow to recover from concussion, as there is little research in this area, and none focused on youth. 14,15,27–29 To our knowledge, no previous study has prospectively assessed longitudinal trajectories of post-concussive and depressive symptoms in a pediatric population of patients who remain symptomatic from concussion after the acute recovery period.…”
Section: Introductionmentioning
confidence: 99%